Lipoxygenase activation in peanut seed cultivars resistant and susceptible to Aspergillus parasiticus colonization - Muller, Virginia (2014)
Accumulative evidence indicates that the lipoxygenase (LOX) pathway plays a significant role in the Aspergillus–seed interaction, such as interfering with activities of endogenous fungal oxylipins or producing antimicrobial compounds and signaling molecules. In this study, we characterized the LOX pathway in peanut seed during Aspergillus parasiticus colonization in a model of two cultivars distinguished as resistant (‘PI337394’) and susceptible (‘Florman INTA’) to Aspergillus spp. infection and aflatoxin contamination. The LOX activity together with the content of LOX substrate and LOX products demonstrated the presence of a differential response mechanism to A. parasiticus infection between cultivars. Our findings suggest that this mechanism is under transcriptional control of previously identified (LOX 2 and LOX 3) and novel (LOX 4 and LOX 5) LOX genes. The results of this study support the role of these enzymes in defense during fungus infection in peanut seed.